Hall MHD simulations of MARFE movements in limiter and divertor configurations - Yiming Zu; Zhiwei Ma; Wei Zhang; Wenjin Chen; Yuchen Xu; Ge Zhuang (Nuclear Fusion)
MARFE movements in limiter and divertor configurations are studied using impurity Hall MHD code CLT. We simulate the MARFE movement experiment on J-TEXT and validated the simulation by comparing the line-averaged density and line radiation intensity between the simulation and the experiment. It is found that impurity radiation cooling enhances the Hall effect, leading to the MARFE movement. Impurity radiation cooling causes the locally enhanced distribution of the current density. When the enhanced current approaches close to the q = 2 resonant surface, the tearing mode is excited. We also simulated MARFE movement in a lower divertor configuration with the X-point. The results show that the impurity radiation cooling at the X-point generates a clockwise poloidal velocity flow towards the high-field side. This velocity is mainly driven by the impurity radiation cooling while the Hall effect can be ignorable. When the temperature cooling is strong, this poloidal velocity is significant enough to drive MARFE towards the high-field side. Otherwise, MARFE remains located at the X-point.